Adapt or withdraw? Evidence on technological changes and early retirement using matched worker-firm data - Torbjørn Hægeland; Dag Rønningen; Kjell G. Salvanes (Statistics Norway, Research Department, 2007)
Older workers typically possess older vintages of skills than younger workers, and they may suffer more from technological change. Experienced workers may nevertheless have accumulated human capital making them suitable for adopting new technologies. On the other hand, to adjust to new technologies, workers must invest in training. This may not be worthwhile for the oldest workers, and technological change may thus induce early retirement. If technological change occurs often, workers will continuously invest in training, which may insulate them from the negative effect of technological change. We exploit the approach by Bartel and Sicherman (1993) to identify this effect by estimating the retirement response to technological change. We examine two hypotheses about the effects of technological changes on early retirement for workers from the age of 50 to the mandatory age of retirement at 67. First, we examine whether workers in firms with higher rates of anticipated technological change retire later than workers in firms with lower rates of technological change. Second, we examine if unanticipated technological change is positively correlated with earlier retirement. We use a matched employer-employee data set with a rich set of controls for worker, firm and local labour market characteristics, and firm level measures of anticipated and not-anticipated technological change. We find a negative correlation between early retirement and anticipated technological change only for the oldest male workers (62 to 66). Further, we find a higher probability of transition to retirement for workers above 60 for firms introducing new process technologies.
Keywords: 330; Technological changes; early retirement